1973
DOI: 10.1111/j.1399-3054.1973.tb04799.x
|View full text |Cite
|
Sign up to set email alerts
|

Spring Mobilization of Protein Nitrogen in Apple Bark

Abstract: Mobilization of protein nitrogen in the spring was studied in bark of stems of unringed and double stem-ringed apple rootstocks M.7 given different nitrogen treatments.A ready protein hydrolysis occurred; the proteins contributed the greater part of the storage nitrogen exported to tlie growing parts. Protein hydrolysis was little affected by the suppjy of newly absorbed nitrogen. Movement of nitrogen out of the bark between the rings could not be demonstrated. Protein breakdown in the isolated bark sections w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
29
0
1

Year Published

1974
1974
1992
1992

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(31 citation statements)
references
References 16 publications
1
29
0
1
Order By: Relevance
“…Isotopic N has been used in several studies to trace the movement of previously assimilated N to the current year's growth (e.g., Weimbaum and Muraoka, 1986 Millard and Neilsen (1988 Millard and Neilsen (1988 (Tromp and Ovaa, 1973). …”
Section: Introductionmentioning
confidence: 99%
“…Isotopic N has been used in several studies to trace the movement of previously assimilated N to the current year's growth (e.g., Weimbaum and Muraoka, 1986 Millard and Neilsen (1988 Millard and Neilsen (1988 (Tromp and Ovaa, 1973). …”
Section: Introductionmentioning
confidence: 99%
“…Storage proteins in fruit trees have received little attention until quite recently, although in apple trees there is a fund of information emerging. Although the presence of an arginine-rich protein has been reported in apple shoot bark (8,10), storage proteins have only been partially characterized.…”
Section: Introductionmentioning
confidence: 99%
“…During the time that leaves are exporting amino acids, arginine increases greatly in the xylem sap and in the shoot's woody tissues (15,16). In the spring, argininenitrogen accounts for more than 70% of the soluble nitrogen in the wood of an apple tree (7) and constitutes a large percentage of protein-nitrogen as well as soluble nitrogen in the bark tissues (17). The spring increase in soluble, free arginine in bark tissue is greater than can be attributed to the release of arginine from protein, suggesting that arginine is synthesized in bark tissue in the spring (17).…”
mentioning
confidence: 99%
“…In the spring, argininenitrogen accounts for more than 70% of the soluble nitrogen in the wood of an apple tree (7) and constitutes a large percentage of protein-nitrogen as well as soluble nitrogen in the bark tissues (17). The spring increase in soluble, free arginine in bark tissue is greater than can be attributed to the release of arginine from protein, suggesting that arginine is synthesized in bark tissue in the spring (17). Recent work has shown that apple-stem tissue has the ability to interconvert ornithinecitrulline-arginine at any time in the year but with a greater rate in the spring (5).…”
mentioning
confidence: 99%
See 1 more Smart Citation